2022
DOI: 10.1155/2022/4330251
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Grass Carp GIPR and Effect of Nutrition States, Insulin, and Glucagon on Its Expression

Abstract: GIP plays an important regulatory role in glucose and lipid metabolism. As the specific receptor, GIPR is involved in this physiological process. To assess the roles of GIPR in teleost, the GIPR gene was cloned from grass carp. The ORF of cloned GIPR gene was 1560 bp, encoding 519 amino acids. The grass carp GIPR was the G-protein-coupled receptor which contains seven predicted transmembrane domains. In addition, two predicted glycosylation sites were contained in the grass carp GIPR. The grass carp GIPR expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In the present study, induced overfeeding increased the ccdc3 expression considerably in the hepatopancreas, brain, and visceral fat tissues. Meanwhile, our previous study showed that visceral fat accumulation in grass carp can be induced by overfeeding (Yang, Liang, Jiang, Li, Zhang, et al, 2022). Furthermore, the ccdc3 mRNA level in primary hepatocytes can be increased by treatment with oleic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, induced overfeeding increased the ccdc3 expression considerably in the hepatopancreas, brain, and visceral fat tissues. Meanwhile, our previous study showed that visceral fat accumulation in grass carp can be induced by overfeeding (Yang, Liang, Jiang, Li, Zhang, et al, 2022). Furthermore, the ccdc3 mRNA level in primary hepatocytes can be increased by treatment with oleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Induced overfeeding and fasting and refeeding experiments were performed to assess the nutritional status of grass carp and ccdc3 expression. The experimental procedure of induced overfeeding was set by referring to our previous study (–, Liang, Jiang, Li, Zhang, et al, 2022). Healthy grass carp (26.24 ± 0.88 g) were assigned to control and induced groups (three tanks per group).…”
Section: Methodsmentioning
confidence: 99%